2017
DOI: 10.1371/journal.pone.0183706
|View full text |Cite
|
Sign up to set email alerts
|

Elevated neutrophil to lymphocyte ratio and ischemic stroke risk in generally healthy adults

Abstract: Elevated neutrophil to lymphocyte ratio (NLR) has been reported as a marker for chronic inflammation, associated with poor prognosis in ischemic stroke patients, but there has been no study that investigated its association with ischemic stroke risk. This study was conducted to investigate elevated NLR as an independent risk factor for ischemic stroke incidence. Our retrospective cohort study included 24,708 generally healthy subjects aged 30–75 who received self-referred health screening at Seoul National Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 24 publications
(32 reference statements)
4
44
1
Order By: Relevance
“…The neutrophil : lymphocyte ratio is increasingly recognized for its prognostic value in cardiovascular disease, infection, inflammatory diseases, and several types of cancer 21,22 ; an increased neutrophil : lymphocyte ratio was shown to predict a poorer prognosis, 21 although a normal range is yet to be determined. However, the unprecedented finding of an increased neutrophil : lymphocyte ratio in the absence of any abnormalities may suggest an additional adaptive process that occurs in response to training.…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil : lymphocyte ratio is increasingly recognized for its prognostic value in cardiovascular disease, infection, inflammatory diseases, and several types of cancer 21,22 ; an increased neutrophil : lymphocyte ratio was shown to predict a poorer prognosis, 21 although a normal range is yet to be determined. However, the unprecedented finding of an increased neutrophil : lymphocyte ratio in the absence of any abnormalities may suggest an additional adaptive process that occurs in response to training.…”
Section: Discussionmentioning
confidence: 99%
“…The medical model characterized by prediction, prevention, personalization and participation has gained greater prominence [1]. Some research has explored the individual differences between healthy population and associated disease risks [2,3]. However, it is not clear whether the normal healthy population, within a specific ethnic identity, can be classified into distinctive groups, where each group exhibits its own biological features and disease risks.…”
Section: Introductionmentioning
confidence: 99%
“…Tokgoz et al reported that the NLR at the time of hospital admission might be a predictor of short-term mortality independent of infarct volume in patients with AIS [42]. Furthermore, the NLR has been reported to be an independent risk factor for the incidence of AIS in generally healthy populations [2]. In our study, the NLR and the total WBC count were significantly higher in the poor outcome group than in the good outcome group, similar to results reported in other studies [23,24,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that inflammation plays an important role in various atherosclerotic disorders [2,3]. Elevated blood inflammatory markers such as high sensitivity C-reactive protein (hs-CRP) have been shown to be independent risk factors for cardiovascular disease and ischemic stroke [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation